Bothersome Hematospermia Following Stereotactic Body Radiation Therapy for Prostate Cancer - Shah, Sarthak; Sholklapper, Tamir; Creswell, Michael; Pepin, Abigail; Cantalino, Jonathan; Hankins, Ryan Andrew; Suy, Simeng; Collins, Sean P. (Frontiers in Oncology, 2021)
Background: Hematospermia following prostate radiation therapy is a benign and often self- limiting side effect. However, it may be bothersome to some men and their partners with a negative impact on sexual quality of life (QOL). This study sought to evaluate the incidence, duration, and resolution of hematospermia in patients following stereotactic body radiation therapy (SBRT) for prostate cancer Methods: 227 patients treated with SBRT from 2013 to 2019 at Georgetown University Hospital for localized prostate carcinoma with a minimum follow up of two years were included in this retrospective review of data that was prospectively collected. Patients who were greater than 70 years old and/or received hormonal therapy were excluded. Hematospermia was defined as bright red blood in the ejaculate. Time points for data collection included initial consultation, pre-treatment, 1-, 3-, 6-, 9-, 12-, 18-, 24-month. All patients were treated with the CyberKnife Radiosurgical System (Accuray). Data on hematospermia including duration, resolution and recurrence was collected. Utilization of 5-alpha reductase inhibitors was documented at each visit. Results: 227 patients (45 low-, 177 intermediate-, and 5 high-risk according to the D’Amico classification) at a median age of 65 years (range 47-70) received SBRT for their localized prostate cancer. The 2-year cumulative incidence of hematospermia was 5.6%. For these patients, all but one patient (93%) saw resolution of their hematospermia by two years post- SBRT. The median time for hematospermia was 9 months post-treatment. Of the 14 patients who reported hematospermia, 70% were managed with 5-alpha reductase inhibitors. Hematospermia was transient in most patients with 70% of the men reporting resolution by the next follow-up visit. Conclusion: The incidence of bothersome hematospermia following SBRT was low. Hematospermia, as noted by other studies, often self-resolves. 5-alpha reductase inhibitors may lead to quicker resolution of bothersome hematospermia.